2022
DOI: 10.3389/fimmu.2021.745111
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Regulates FKBP4/NR3C1/NRF2 Axis in Autophagy and Proliferation of Breast Cancer and Differentiation and Maturation of Dendritic Cell

Abstract: NRF2 is an important regulatory transcription factor involved in tumor immunity and tumorigenesis. In this study, we firstly identified that FKBP4/NR3C1 axis was a novel negative regulator of NRF2 in human breast cancer (BC) cells. The effect of FKBP4 appeared to be at protein level of NRF2 since it could not suppress the expression of NRF2 at mRNA level. Bioinformatics analysis and in vitro experiments further demonstrated that FKBP4 regulated NRF2 via regulating nuclear translocation of NR3C1. We then report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Our previous work found that FKBP4 could bind to NR3C1 and regulate nuclear translocation of NR3C1, 38 with the above findings that FKBP4 regulated TMEM173 promoter, we wondered whether NR3C1 affected the expression of TMEM173 at the transcriptional level. Results showed siRNA specifically targeting NR3C1 decreased TMEM173 promoter activity in BT549 cells, while NR3C1-HA plasmid promoted TMEM173 promoter activity in BT549 cells ( Figure 3 D); therefore, NR3C1 was found to have a positive impact on regulating TMEM173 promoter.…”
Section: Resultsmentioning
confidence: 95%
“…Our previous work found that FKBP4 could bind to NR3C1 and regulate nuclear translocation of NR3C1, 38 with the above findings that FKBP4 regulated TMEM173 promoter, we wondered whether NR3C1 affected the expression of TMEM173 at the transcriptional level. Results showed siRNA specifically targeting NR3C1 decreased TMEM173 promoter activity in BT549 cells, while NR3C1-HA plasmid promoted TMEM173 promoter activity in BT549 cells ( Figure 3 D); therefore, NR3C1 was found to have a positive impact on regulating TMEM173 promoter.…”
Section: Resultsmentioning
confidence: 95%
“…Several mechanisms have been implicated in the inhibition of cell proliferation: (i) inhibition of the activity of tyrosine-specific protein kinases [ 126 , 127 , 128 ], such as inhibition of PKC, which is one of the key enzymes in the regulation of cellular proliferation and tumor growth; (ii) induction of the differentiation of carcinoma cells [ 3 , 13 , 126 , 127 , 128 , 129 ]; (iii) transcriptional changes in cell cycle- and apoptosis-related genes such as NF-κB, Bcl-X(L) and COX-2; (iv) binding to the estrogen receptor and inhibition of an estrogen receptor-positive human breast cancer cells [ 130 , 131 ]; (v) induction of apoptosis, (vi) downregulation of the expression of mutated H-Ras and p53 tumor suppression gene [ 3 , 13 , 126 ], (vii) modulation of gene methylation and re-expression of tumor suppressors or other genes silenced by aberrant DNA methylation [ 119 , 130 , 131 ], (viii) inhibition of pro-oxidative enzymes xanthine oxidase, cyclooxygenases, or lipooxygenases [ 3 , 13 , 126 , 127 ], and (ix) some flavonoids are a direct poison for topoisomerase II (TopoII), through the stabilization of double strand breaks in the TopoII-DNA cleavage [ 4 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…For example, autophagy induced in apoptosis-resistant tumors can be important in the prevention of tumor formation, but it can be negative in an advanced stage of the tumor and enable the survival of tumor cells and the development of resistant cells to various forms of therapy, including chemotherapy and radiotherapy. Moreover, activation of the Nrf2 signaling pathway by propolis and flavonoids in the late phase of tumor development can contribute to resistance to chemo- and radiotherapy [ 127 , 140 , 141 , 142 , 241 , 250 ]. Furthermore, different sensitivity of tumor cells was confirmed depending on the different stages of tumor development.…”
Section: Present Status and Future Perspectivesmentioning
confidence: 99%
“…In experiments with neuroblast cells, nuclear translocation of the GR during cortisol treatment was inhibited by the knockdown of FKBP52 43 . However, in breast cancer cell lines, the relationship between FKBP52 and GR is reversed, FKBP52 binds to the GR and inhibits its nuclear translocation 44 . These results suggest that GR regulation by FKBP52 could differ among cell types.…”
Section: Activation Mechanism Of Interacting Moleculesmentioning
confidence: 97%